Penguatan Moderasi Beragama di Pesantren Al Tahfidz dan Alim RPYD Darul Khairat Sawit Rejo Kecamatan Kutalimbaru Kabupaten Deli Serdang - Bakti, Surya; Hemawati, Hemawati; Arbeni, Wawan; Rangkuti, Ahmad Zuhri; Najari, Muhammad; Siswan, Heri; Akbar, Muhammad Dirja (Universitas Pahlawan Tuanku Tambusai, 2025)
As an effort to maintain the security of the Republic of Indonesia through the implementation of religious moderation, this community service activity aims to provide education on strengthening religious moderation to students at the Tahfidz and Alim RPYD Darul Khairat Islamic Boarding School, Sawit Rejo, Kutalimbaru, Deli Serdang. This activity was carried out using the Participatory Action Research (PAR) method to build understanding of tolerance and prevent potential disputes due to intolerance. As a result, this programme succeeded in strengthening the students' understanding of religious moderation and made the Islamic boarding school a institutional partner of the Syekh Abdul Halim Hasan Binjai Institute in the development of religious moderation.